A Decision‐Making Model for Addressing Problematic Behaviors in Counseling Students. Issue 2 (October 2016) - Letourneau, Jade L. H.
Abstract : Gatekeeping is the subject of continued discourse in the counseling profession. With revisions to the ACA Code of Ethics (American Counseling Association, 2014 ), recent litigation ( Keeton v. Anderson‐Wiley, 2010 ; Ward v. Wilbanks, 2009 ), and focused attention on value conflicts in counseling (Francis & Dugger, 2014 ), counselor educators' role as gatekeepers is expanding. In addition to this expanding role, counselor educators are responsible for being culturally and developmentally sensitive in interpreting, applying, and enforcing the codes and standards with counseling students. This article proposes a decision‐making model that integrates feminist, multicultural, systems theory, and social‐constructivist ethical decision‐making principles to address problematic behaviors in counseling students.